2014
DOI: 10.1371/journal.pone.0092664
|View full text |Cite
|
Sign up to set email alerts
|

Three Weeks of Murine Hindlimb Unloading Induces Shifts from B to T and from Th to Tc Splenic Lymphocytes in Absence of Stress and Differentially Reduces Cell-Specific Mitogenic Responses

Abstract: Extended space missions are known to induce stress and immune dysregulation. Hindlimb unloading is a ground-based model used to reproduce most spaceflight conditions. The aim of this study was to better characterize the consequences of prolonged exposure to hindlimb unloading on murine splenic lymphocyte sub-populations. To ensure that the observed changes were not due to tail restraint but to the antiorthostatic position, three groups of mice were used: control (C), orthostatic restrained (R) and hindlimb unl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
41
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 53 publications
9
41
0
2
Order By: Relevance
“…While such an exposure may cause stress to the animal, no difference in serum corticostrone levels between experimental and control groups of mice were found, suggesting a low state of stress or adaptation. However, in agreement with our observations regarding CMS exposure, the study found that hindlimb unloading lead to an inversion of the B:T ratio in the spleen [28]. In our study, mice housed in EE-conditions show more accentuated responses upon exposure to stress, such as higher increases in FCM levels, suggesting that these mice were less stressed and thus able to mount a higher HPA axis stress response than mice housed in Cntl-caged environment.…”
Section: Discussionsupporting
confidence: 92%
“…While such an exposure may cause stress to the animal, no difference in serum corticostrone levels between experimental and control groups of mice were found, suggesting a low state of stress or adaptation. However, in agreement with our observations regarding CMS exposure, the study found that hindlimb unloading lead to an inversion of the B:T ratio in the spleen [28]. In our study, mice housed in EE-conditions show more accentuated responses upon exposure to stress, such as higher increases in FCM levels, suggesting that these mice were less stressed and thus able to mount a higher HPA axis stress response than mice housed in Cntl-caged environment.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, unlike the detrimental effects of chronic stress, short‐term acute stressors appear to increase immunity (50). As observed in other studies, HU mice had a lower body mass compared with controls (12, 27, 28). Energy intake and expenditure, despite the provision of food in sufficient amounts, is a likely explanation to this observation.…”
Section: Discussionsupporting
confidence: 87%
“…We also studied the evolution of body weight during the experimental period. As noted by others (12,27,28), HU mice lost approximately 10% body weight in the first 2 d and their weight remained below that of controls during the 21 d of HU (Fig. 1B).…”
Section: Kinetics Of Bone Microarchitectural Alterations and Evaluatisupporting
confidence: 83%
“…Antiorthostatic suspension (AOS) is one of well-known ground based model of simulated microgravity [1]. We could perform AOS experiment by simply hanging the tail of mouse so that the hindlimbs are not bearing weight.…”
Section: Introductionmentioning
confidence: 99%
“…We could perform AOS experiment by simply hanging the tail of mouse so that the hindlimbs are not bearing weight. Using their forelimbs on the ground, animal could move and get food and water [1]. Several researchers have suggested that AOS could reproduce the effect of real microgravity on the cardiovascular, musculoskeletal, and more importantly, immune systems of a living organism [2-4].…”
Section: Introductionmentioning
confidence: 99%